Application of the Economic Value Added (EVA) Concept as a Measuring Tool for Financial Performance - Nianty, Dara Ayu; Safitri, Putri Aulia (Advances in Economics & Financial Studies, 2023)
This study aims to determine the application of Economic Value Added (EVA) to financial performance at PT. XL Axiata, Tbk. The sample in this study is the financial performance of PT. XL Axiata, Tbk for three years. This research method uses the documentation method. The data used in this study is secondary data obtained from financial reports on the Indonesian Stock Exchange website. The data obtained is then processed by simple regression. Based on the analysis that has been done, it can be concluded that the financial performance of PT. XL Axiata, Tbk. This can be seen from the EVA value, which continuously decreases yearly until it reaches a negative EVA value so that PT. XL Axiata, Tbk could not generate returns per the expectations of shareholders. Also, evaluating financial performance using the EVA method strongly supports assessing financial performance based on financial ratios. This performance appraisal method gives the result that PT. XL Axiata has continuously experienced a decline in financial performance. However, with EVA, shareholders can see the size of the return generated by PT. XL Axiata Tbk for shareholders and whether the rate of return follows the shareholders' expectations, exceeding the cost of capital for the investment it makes